f(x)=9xsquared+5x+1

Simple and best practice solution for f(x)=9xsquared+5x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(x)=9xsquared+5x+1 equation:


Simplifying
f(x) = 9xsquared + 5x + 1

Multiply f * x
fx = 9xsquared + 5x + 1

Reorder the terms:
fx = 1 + 9adeqrsux + 5x

Solving
fx = 1 + 9adeqrsux + 5x

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Divide each side by 'x'.
f = x-1 + 9adeqrsu + 5

Simplifying
f = x-1 + 9adeqrsu + 5

Reorder the terms:
f = 5 + 9adeqrsu + x-1

See similar equations:

| 2[x+8]=-4[5x-2]+8x | | 2x-7+4x+15=56 | | (4x-7)+(-12-8x)= | | 3+25x=20x+12 | | 15-4t=4 | | 3+25x=20x-12 | | e^4x=10 | | 2z(z)+20z=0 | | 3+25x=2-0x+12 | | 34+(25x)+(35x)=93 | | 34+(25x)+(35x)=94 | | (1+i)*z*z+2iz-1=0 | | 34+(25x)+(35x)=90 | | 34(25x)(35x)=90 | | 2z+20z=o | | 55-3x=6-10x | | 4x+15=-5x-12 | | 2x-5+57=3x+9 | | 5y+6-9y= | | 9x+17=4x+42 | | 13=4x-15 | | -6+(-1-b)=19 | | m^2+3=4 | | A=-3a-16 | | 3r^2=-45 | | cos(c)+3*sin(c)=2 | | x=22y+39x | | 4x-5=6x+23 | | Log[2](3x+8)=5 | | 3x-2=-5x-6 | | -h^2+15h+50=0 | | -61= |

Equations solver categories